2018
DOI: 10.1007/s13258-018-0672-6
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate genome-wide association studies on tenderness of Berkshire and Duroc pig breeds

Abstract: Genome-wide association studies (GWAS) have been steadily used for identification of genomic links to disease and various economical traits. Of those traits, a tenderness of pork is one of the most important factors in quality evaluation of consumers. In this study, we use two pig breed populations; Berkshire is known for its excellent meat quality and Duroc which is known for its high intramuscular fat content in meat. Multivariate genome-wide association studies (MV-GWAS) was executed to compare SNPs of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The Berkshire pig was known for its high-quality meat ( Jang et al, 2018 ) and adaptation to semi-grazing conditions. Landrace pigs, on the contrary, claimed to have a high growth rate ( Tang et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Berkshire pig was known for its high-quality meat ( Jang et al, 2018 ) and adaptation to semi-grazing conditions. Landrace pigs, on the contrary, claimed to have a high growth rate ( Tang et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Duroc is one of the most popular sire breeds in pig breeding. It is excellent in growth rate, body composition, and it is famous for high intramuscular fat content in meat [27,28]. Selection for the best sire individuals is a most time and money consuming work in pig breeding, and furthermore, how to preserve and make full use of this super boar after picking up the best sire in the population is another question.…”
Section: Discussionmentioning
confidence: 99%
“…Indoor enrichment (more space, straw bedding) generally improved pig meat juiciness and flavor through higher IMF concentration ( Lebret, 2008 ). Berkshire pigs, known for their high-quality meat and adaptation to semi-grazing conditions ( Jang et al, 2018 ), were shown to have increased fat area in muscle and adipose tissue and the myofiber density significantly in the pigs of the free grazing farm group. The relative abundance of bacteria associated with lipid metabolism (such as Oscillibacter ) and probiotic function ( Lactobacillus and Clostridium ) was also higher ( Qi et al, 2019 ).…”
Section: Different Rearing Systems and Microbiotamentioning
confidence: 99%